Formação cultural e artística de estudantes de pedagogia: constelações potenciais - Bonci, Estela Maria Oliveira (2018)
As a map of the night sky, a celestial chart was drawn for the journey through the constellations present in the universe of the cultural and artistic formation of the Pedagogy students of the Mackenzie Presbyterian University. Ethnographic research sought to formulate hypotheses, concepts and theories, describing and transcribing lived experiences (not its testing or tabulation) to understand and understand the development of communicative processes in their different languages, in order to try to apprehend the reality in the own interaction with the environment and with the research subjects. Its main objective was to unveil the marks in the cultural and artistic formation of the students of the Pedagogy course, with a specific look at the disciplines that focus art and culture on the undergraduate curriculum and to map how these brands contribute as a foundation for the practice of teaching as a practice sensitive, creative and interdisciplinary. In order to do this, the cultural and artistic references that the students bring to the Pedagogy, the cultural and artistic formation that they learn during the course and what they take of this formation upon leaving the graduation were investigated. We talk with authors such as Certeau (1995), Canclini (1998), Paulo Freire (1996 and 1980), Nogueira (2008 and 2010), among others on concepts of culture, art and cultural and artistic formation. We used Dewey (2011), Larrosa (2002 and 2004), Barbosa (2008), Martins (1998, 2007, 2014), Eisner (2008), Hernández (2000), Irwin (2013 and 2014), Tardif (2014), Sacristan (2002), Gatti; Barretto and André (2011), Santomé (1995) to reflect on teaching art and teaching, in addition to the contributions of GPAP / Research Group Art in Pedagogy (2015). Data were collected over a period of three years (2015, 2016 and 2017), from classroom observation, specific questionnaires, practical interventions, interviews, documents and productions of the students participating in the research. It was possible to understand cultural and artistic formation as an articulating thread for the exercise of a sensitive and creative teaching, mediated by art and by the awareness and intentionality of a pedagogical practice that is a carrier and creator of culture, plural and transformative. The marks of aesthetic experiences in contact with art and culture are presented as potentials for teaching, both in the sense of valuing the experiences made aware and the mediators that made them possible, as well as the perception of the challenges to be overcome in the process of cultural and artistic formation of students of Pedagogy. In this journey, perceptions about art, culture, knowledge and the potentiality of the curriculum are revealed and expanded as propositions inviting reflection on the pedagogical practices developed in the classrooms of Pedagogy courses.